Analysis of Fulfillment of Socio-Economic Rights in Under Developed Areas : A Study of Rote Ndao District - Marthen Lona (International Journal of Economics, Management and Accounting, 2024)
This study aims to analyze the implementation of the fulfillment of socio-economic rights of the community in Rote Ndao Regency, as one of the underdeveloped regions in Indonesia, and to identify the obstacles faced by the local government in its efforts to fulfill them. Socio-economic rights, such as access to education, health, employment, and public services, are part of the human rights guaranteed by the constitution. However, their implementation often encounters various obstacles in areas with less developed socio-economic conditions. This study uses a qualitative method with a descriptive analytical approach. Data were collected through in-depth interviews, document studies, and field observations. The results of the study indicate that the implementation of socio-economic rights in Rote Ndao Regency is still not optimal. This can be seen from the low level of community access to educational facilities, health services, and basic infrastructure. On the other hand, the local government faces a number of significant obstacles, such as budget constraints, lack of adequate infrastructure, low quality of human resources, geographical barriers, and weak coordination between agencies. As a solution, this study recommends increasing budget allocations for priority sectors, developing basic infrastructure, improving the quality of human resources through education and training, and strengthening cross-sectoral coordination. In addition, active community involvement in the planning and implementation of development programs is also very important to improve the effectiveness of policies. The results of this study are expected to contribute to local governments and other stakeholders in formulating more effective strategies to accelerate the fulfillment of people's socio-economic rights, while improving the quality of life in Rote Ndao Regency.